Kunci Keberhasilan: Bagaimana Motivasi dan Gaya Belajar Mempengaruhi Prestasi Mahasiswa Fakultas Ekonomi Universitas Negeri Jakarta (International Forum of Researchers and Lecturers, 2023)
The purpose of this research is to determine the influence of learning motivation and style in learning on learning outcomes. The type of research that will be carried out is using quantitative research methods with descriptive analysis. Data collection was carried out through a questionnaire which was measured using a Likert scale from one to five for 100 respondents with the criteria being students aged 18-22 years. The data analysis technique that will be used in this research is the Outer Model with calculations of Convergent Reliability, Discriminant Validity, Composite Reliability, Cronbach's Alpha and Inner Model with T statistics, R-Square and VIF calculations using SmartPLS 4 tools. The results of the research show that learning motivation influences learning achievement because of the accuracy factor in collecting assignments, this has high motivation. Learning style has no effect on learning achievement because it is caused by the very minimal study time that students spend. Apart from that, learning motivation and learning style together influence student learning achievement.